Climate Security Programming Dashboard for Climate Finance (CSPDxCF): Guidebook and methodology - Scartozzi, Cesare Marco; Caroli, Giulia; Sarzana, Carolina; Läderach, Peter R.D.; Pacillo, Grazia; Elnur, Rawie Ibrahim; Hyslop, Daniel; Hahn, Andreas Luis; Azar, Elio (2023)
The Climate Security Programming Dashboard for Climate Finance (CSPDxCF) represents a novel, comprehensive tool designed to assist international financial institutions and climate funds in conducting conflict-sensitive assessments and receiving tailored guidance for their funded projects. This innovative platform serves three primary functions: Prepare, Integrate, and Optimize. In the 'Prepare' phase, CSPDxCF enables project evaluators to discern the strengths and weaknesses of proposed initiatives during the origination and preparation stages, ensuring a robust foundation for project development. The 'Integrate' phase focuses on the amalgamation of climate strategies with peace-informed programming, a critical step towards mitigating operational risks and bolstering peace outcomes. Finally, in the 'Optimize' phase, users are provided with personalized guidance aimed at maximizing fund allocation efficiency and enhancing the overall effectiveness of projects in fragile and conflict-affected settings. CSPDxCF thus stands as a pivotal tool in the realm of climate finance, offering a structured and insightful approach to fostering sustainable, peace-centric climate projects in challenging environments.